PELAYANAN PRIMA PADA RUMAH SAKIT UMUM MILIK PEMERINTAH DI JAWA (Studi di Rumah Sakit Umum Pusat Dr. Kariadi Semarang, Rumah Sakit Umum Daerah Dr. Soetomo Surabaya, dan Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung) - Hesti Lestari (Magister Administrasi Publik, FISIP, 2021)
Hospital services are basically a form of service provided to patients by paying attention to predetermined service quality standards, in order to create satisfaction for patients in accordance with patient expectations. Central General Hospital Dr. Kariadi Semarang, Regional General Hospital Dr. Soetomo Surabaya, and Central General Hospital Dr. Hasan Sadikin Bandung is a government-owned public hospital located in the Java region. The three hospitals are government-owned hospitals as national referral hospitals which are class A hospitals. The purpose of this research is to find out how the form of excellent service and the advantages and disadvantages of the Central General Hospital Dr. Kariadi Semarang, Regional General Hospital Dr. Soetomo Surabaya and Central General Hospital Dr. Hasan Sadikin Bandung. The research method used the desk-review method, namely the collection of secondary data or data that has been previously collected without conducting a field survey and library research methods. Besides that, this research also uses literature study, namely collecting scientific papers or collecting data related to the object of research or collecting library data. The form of excellent service carried out by the Central General Hospital Dr. Kariadi Semarang, Regional General Hospital Dr. Soetomo Surabaya and Central General Hospital Dr. Hasan Sadikin Bandung is about speed of service, accuracy of service, accurate service and quality of service. Each hospital has problems regarding the speed of service, so that the speed of service is a priority for improvement for hospitals to realize excellent service in accordance with patient expectations.